2022
DOI: 10.1155/2022/9716045
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Family with Brugada Syndrome and Sudden Cardiac Death Caused by a Novel Mutation of SCN5A

Abstract: Background. Brugada syndrome is a hereditary cardiac disease associated with mutations in ion channel genes. The clinical features include ventricular fibrillation, syncope, and sudden cardiac death. A family with Brugada syndrome with sudden cardiac death was analyzed to locate the associated mutation in the SCN5A gene. Methods and Results. Three generations of a Han Chinese family with Brugada syndrome were recruited in the study; their clinical phenotype data were collected and DNA samples extracted from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…According to a study conducted by Zhu et al, BrS, also known as unexplainable sudden death syndrome, is the primary cause of sudden death in young people and affects as many as four to 10 individuals per 10,000 in the general population. The findings from this epidemiological study indicate that BrS is responsible for SCD in nearly 50% of young individuals in South Asia who have nonstructural heart disease [18]. The syndrome is likely to be the cause of 4% of all SCD cases and 20% of SCD patients who do not have structural heart disease.…”
Section: Complications and Risk Stratificationmentioning
confidence: 75%
See 2 more Smart Citations
“…According to a study conducted by Zhu et al, BrS, also known as unexplainable sudden death syndrome, is the primary cause of sudden death in young people and affects as many as four to 10 individuals per 10,000 in the general population. The findings from this epidemiological study indicate that BrS is responsible for SCD in nearly 50% of young individuals in South Asia who have nonstructural heart disease [18]. The syndrome is likely to be the cause of 4% of all SCD cases and 20% of SCD patients who do not have structural heart disease.…”
Section: Complications and Risk Stratificationmentioning
confidence: 75%
“…Aborted SCD, syncope, seizures, and nocturnal agonal breathing are among the symptomatic manifestations. Malignant syncope can increase the risk of SCD in people who have spontaneous type one Brugada waves [18]. The risk of SCD is approximately four times higher in persons with a history of syncope than in those with no history of syncope.…”
Section: Complications and Risk Stratificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other mutations in sodium, potassium and calcium channels are responsible for the pathogenesis of BrS in 5% of cases. Besides, even in the known cases with mutations of SCN5A, incomplete penetrance and variable expressivity lead to diverse phenotypes in family members with the same mutations [7,8]. A recent study has demonstrated that mutations in the cholesterol-and fibrosis-related genes caused more severe phenotypes in patients with mutations of ion channels [8].…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, during initial evaluation, our proband experienced SCA and earlier syncopal episode during physical activity, which is more typical for arrhythmogenic right ventricular cardiomyopathy (ARVC) [42]. However, it should be noted that there were cases of SCA (VF while running [43]) or sudden death (SCN5A mutation carrier [44]) of patients with BrS during or after exercise described. As previously reported by us in detail, the presented patients highlight how challenging the determination of the etiology and management of syncopal and/or presyncopal episodes [45,46] can be, and that unusual triggers, such as physical exercise, may also contribute to SCD among patients with BrS.…”
Section: Characteristics Of the Patientsmentioning
confidence: 98%